2014
DOI: 10.1097/cad.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

3-Acetyl-bis(2-chloro-4-nitrophenyl)triazene is a potent antitumor agent that induces oxidative stress and independently activates the stress-activated protein kinase/c-Jun NH2-terminal kinase pathway

Abstract: Previously, we described the synthesis and biological activity of a new class of anticancer molecules that preferentially target malignant cells and may serve as potential antitumor agents. Among several synthesized agents, we selected 3-acetyl-1,3-bis(2-chloro-4-nitrophenyl)-1-triazene (8b) as a representative of the group of 4-nitro-substituted 1,3-diaryltriazenes. The aim of this study was to further investigate the mechanism of cell response to the 8b compound. The HeLa human cervical carcinoma cell line w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…For that purpose, HeLa cells were either pre-treated with 5 mM NAC, the precursor for GSH synthesis, for 2 h prior to treatment with compound 5 or overnight with a specific inhibitor of GSH synthesis, i.e., 0.001 mM BSO. The conditions used were tested previously to be effective ( Brozovic et al, 2008 ; Brozovic et al, 2014 ). The obtained data showed that an increased level of GSH protects HeLa cells from ragusinin’s toxicity ( Figure 8A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For that purpose, HeLa cells were either pre-treated with 5 mM NAC, the precursor for GSH synthesis, for 2 h prior to treatment with compound 5 or overnight with a specific inhibitor of GSH synthesis, i.e., 0.001 mM BSO. The conditions used were tested previously to be effective ( Brozovic et al, 2008 ; Brozovic et al, 2014 ). The obtained data showed that an increased level of GSH protects HeLa cells from ragusinin’s toxicity ( Figure 8A ).…”
Section: Resultsmentioning
confidence: 99%
“…This redox cycling of GSH plays a role in the maintenance of cellular redox homeostasis. GSH binds to endogenous and diverse xenobiotic electrophilic compounds either catalytically, through the action of glutathione S-transferase, or non-catalytically ( Townsend and Tew, 2003 ; Brozovic et al, 2014 ). The formed GSH conjugates can be exported from cells, resulting in the loss of cellular GSH.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data indicate that diverse compounds can induce cell damage due to formation of ROS. 38 , 39 ROS may irreversibly oxidize DNA, nucleic acids, proteins, and lipids, thereby representing the primary source of damage in biological systems that may eventually lead to cell death. 40 , 41 Accordingly, we directly measured the induction of ROS formation following the treatment with 2b.…”
Section: Resultsmentioning
confidence: 99%
“…For that purpose, HeLa cells were either pre-treated with specific inhibitor of GSH synthesis, 0.01μg/mL buthionine sulfoximine (BSO) overnight or with precursor of GSH synthesis, 5 mM N-acetylcysteine (NAC) for two hours prior to treatment with 2 pG , 2 pA , 2 mG or 2 mA . The conditions used were tested previously to be effective (Brozovic et al 2008, Brozovic et al 2014. The obtained data showed decreased survival of HeLa cells in the case when GSH was depleted by BSO and increased survival of cells in the case when the level of GSH was increased due to the NAC (Figure 5A-D).…”
Section: Cpmentioning
confidence: 87%